Social media, public sphere and reshaping feminism in Nigeria (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
This research aimed to determine whether the use of social media as a public sphere influenced the development of feminism in Nigeria, the extent to which Nigerian Feminism uses social media as a public sphere for shaping and reshaping Feminism, and whether there are additional ways in which social media platforms as a public sphere can be used to promote and reshape feminism in Nigeria. One theoretical framework served as the basis for this study: Media dependency theory. A qualitative research strategy was employed to elicit primary data for a comprehensive understanding of the study. Using a purposive sampling technique, a questionnaire was used as the design instrument to recruit 656 respondents from Nigeria's six geopolitical zones. Findings show that social media has evolved into a new and effective public sphere that fosters and promotes Nigerian Feminism and feminist activism. It is suggested that Nigerian feminists should seek more opportunities to engage with the public sphere of social media to stimulate and propagate Nigerian Feminism and make it more equitable and sustainable. Nigeria must bridge the ever-widening digital divide and illiteracy gap, contributing to the underrepresentation of feminists and marginalized women in Nigeria's social media public sphere.
Keywords: social media; Feminism; Nigeria; Public Sphere; Digital Media